Lewis‐Base‐Induced Disproportionation of a Dialane. Issue 45 (18th July 2018) - Hofmann, Alexander; Lamprecht, Anna; Jiménez‐Halla, J. Oscar C.; Tröster, Tobias; Dewhurst, Rian D.; Lenczyk, Carsten; Braunschweig, Holger
Abstract: The reaction of a pentamethylcyclopentadienyl‐substituted dialane with a variety of Lewis bases results in unexpected disproportionation of the dialane into Al I and Al III species. Use of a transition‐metal Lewis base allows for the formation of metal‐only Lewis pairs. Furthermore, the synthesis of a Lewis base bis‐adduct was successful with the Lewis base 4‐dimethylaminopyridine. Abstract : Aluminum chemistry : The reaction of a pentamethylcyclopentadienyl‐substituted dialane with a variety of Lewis bases is presented, resulting in unexpected disproportionation of the dialane into Al I and Al III species, formation of a metal‐only Lewis pair, and simple base addition.